Growth assessment of individual plants by an adapted remote sensing technique - Casadesús J.; Tambussi E.; Royo C.; Araus J.L. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
The applicability of spectroradiometry to breeding programs could be enlarged if the method was adapted to measure individual plants in early generations of selection. In this study we evaluate the performance of a set-up consisting on a tube with reflecting walls and diffuse illumination for the case of assessing the growth rate of young durum wheat and barley plants from the Normalized Difference Vegetation Index (NDVI). The results showed a strong correlation between NDVI and plant fresh weight (r2 equal to 0.98) and plant green area (r2 equal to 0.95), specially for NDVI less than 0.5. The resolution of the method allowed the quantification of the growth rate of a single plant in a weekly interval.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)